Policy implications of fertilizer subsidy reform - Gupta, Surupa (International Food Policy Research Institute, 2011)
This chapter presents the policy implications of the analysis in the previous sections. Here we consider various options available for changing the policy framework that governs the production of nitrogenous fertilizers in India, as well as for reducing and rationalizing the fertilizer subsidy. Fertilizer policy change and fertilizer subsidy reduction and rationalization have proved extremely difficult for all finance ministers since 1991. Although several policy options have been suggested (HPRC 1998; ERC 2000; Gulati and Narayanan 2003), some of which have been attempted, progress has been marginal. Therefore, it is useful to consider various reform options and assess them for their effectiveness in addressing specific policy goals as well as for their political feasibility. Table 7.1 displays a qualitative assessment of the reform options according to effectiveness, and Table 7.2 contains an assessment of these options and their political feasibility.